DIAGNOSTICS OF UNDERGROUND MASOURY - Baláz, Richard; Toth, Stanislav (International Multidisciplinary Scientific GeoConference SGEM, 2024)
The masonry moisture sanation process does not end, when the building job is over. This article contains results from long-term measurements of moisture levels in underground areas of several old buildings. These results can help in diagnostics and design of repairs in other buildings.